Use of indole-3-acetic acid (IAA) in postharvest of cajá-manga (Spondias dulcis) - Silva, Franciele Cristian da; Santana, Hygor Amaral; Menezes, Juliana Oliveira Silva de; Tavares, Mírian Carvalho; Martins, Rodolfo David; Siqueira, Ana Paula Silva (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2020)
The cajá-manga (Spondias dulcis Parkinson) is an exotic fruit originally from the Polynesian Islands. It is a climacteric fruit, and the postharvest life of its fruits is very short, due to its fast ripening. Thus, this study aimed to evaluate the effect of auxin concentrations on delaying the ripening process of cajá-manga fruits. One hundred twenty cajá-manga fruits obtained from, Hidrolândia-GO, Brazil, at 16°55'32.35" S and 49°21'39.76" W). A completely randomized design in a 5×2+2 factorial scheme was used. Five indole-3-acetic acid (IAA) concentrations (0, 50, 100, 150 and 200 mg L-1), two moments of evaluations (at 5 and 10 days after IAA applications), and two additional treatments (ripe and unripe fruits) were evaluated. Evaluations were carried out every 5 days, in triplicates. The physicochemical variables, pulp firmness, titratable acidity (TA), soluble solids (SS), ascorbic acid content, and color of pulp and peel were evaluated. The concentrations of 50 and 100 mg L-1 of IAA presented the best results, causing a delay in ripening and the lowest sensory losses in the fruits of cajá-manga.